A novel and robust method of indexing the uncoded stripes for multi‐line based structured light application. Issue 25 (16th October 2021) - Xue, Jiawen; Hu, Yi; Li, Guolin; Wang, Zhihua; Xie, Xiang
Abstract: Finding the correspondence between the captured and projected uncoded stripe pattern, which is called the indexing problem, has proved to be difficult to overcome reliably. Due to the interference of the non‐ideal phenomena, the extracted stripe might be lost, increased or shifted undetectably. This letter proposes a graph‐matching based method to address this problem. The captured stripes are categorized into two parts according to whether they should be offset after projection. For the non‐offset stripes, they can be accurately indexed by the predetermined projection pattern. Based on the structural similarity that exists on the two kinds of stripes, we establish two graphs and match them to index the offset stripes fast and effectively. Thus, the iterative process in the previous study is avoided and the troublesome issues are solved. The proposed method is applied to the virtual touchpad scheme to make an arbitrary surface touch‐sensitiveness. Experimental results show that the ameliorated virtual touchpad scheme yields an average touch detection accuracy of 96.07%, and the indexing accuracy evaluated by randomly selected patterns is 100%.